Post-COVID-19 polyautoimmunity – Fact or coincidence: A case report - Shorbagi, Ali Ibrahim; Obaideen, Abdulmunhem; Jundi, Majd (Frontiers in Medicine, 2023)
COVID-19 exhibits diverse and systemic clinical symptoms, much like systemic autoimmune diseases, and there are notable similarities in the immune responses seen in both conditions. There are rare reports of ulcerative colitis and autoimmune hepatitis triggered by COVID-19 infection. Reported herein is a case of a previously healthy patient who was diagnosed with chronic colitis resembling ulcerative colitis, autoimmune pancreatitis, and suspected immune-mediated hepatitis (AIH-like hepatitis) 2 months after a COVID-19 infection. A 33-year-old COVID-19-vaccinated male, presented with abdominal pain, nausea, and vomiting for 2 days. He also had bloody diarrhea that persisted for 2 months after recovering from a COVID-19 infection. A diagnosis of acute pancreatitis was confirmed by markedly elevated serum amylase and lipase and a CT scan of the abdomen. Colonoscopy and histopathology findings also confirmed a diagnosis of chronic colitis resembling ulcerative colitis (Mayo Endoscopy Subscore 3). Marked improvement in bloody diarrhea was observed within 72 h of treatment with IV prednisolone. MRI of the abdomen performed due to an unresolved clinical picture of pancreatitis revealed a bulky pancreas showing delayed diffuse homogenous enhancement, findings possibly consistent with autoimmune pancreatitis. Investigation for elevated liver transaminases showed high titers of antinuclear antibodies and anti-smooth muscle (anti-actin) antibodies while viral hepatitis markers were negative. The patient had already been started on steroid therapy before the lab results were available, with rapid normalization of liver enzymes following treatment. A liver biopsy was not performed. The patient is currently on mesalazine 4 gr/day, and azathioprine 100 mg/day – oral steroids had been tapered and discontinued. Seven months after the initial diagnosis, the patient remains symptom-free. A high level of suspicion for autoimmune disorders is required when assessing patients with a history of COVID-19 infection, although diagnostic pathways remain the same, with generally good response and remission rates to conventional treatment.